2020
DOI: 10.1021/acsomega.0c01867
|View full text |Cite
|
Sign up to set email alerts
|

Sampling Performance of Multiple Independent Molecular Dynamics Simulations of an RNA Aptamer

Abstract: Using multiple independent simulations instead of one long simulation has been shown to improve the sampling performance attained with the molecular dynamics (MD) simulation method. However, it is generally not known how long each independent simulation should be, how many independent simulations should be used, or to what extent either of these factors affects the overall sampling performance achieved for a given system. The goal of the present study was to assess the sampling performance of multiple independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…To carry out a comprehensive molecular docking analysis, diverse representative structures of an unbound aptamer should be considered. Previous works have shown that short independent simulations sample a larger conformational space rather than a unique trajectory. , Furthermore, simulations parting from different initial configurations can explore dynamics and energy basins difficult to sample from a single initial conformation . Therefore, the objective of this study is to assess the binding affinity by molecular docking of metastable representative structures of DNA aptamers obtained from molecular dynamics (MD) simulation of distinct initial conformations.…”
Section: Introductionmentioning
confidence: 99%
“…To carry out a comprehensive molecular docking analysis, diverse representative structures of an unbound aptamer should be considered. Previous works have shown that short independent simulations sample a larger conformational space rather than a unique trajectory. , Furthermore, simulations parting from different initial configurations can explore dynamics and energy basins difficult to sample from a single initial conformation . Therefore, the objective of this study is to assess the binding affinity by molecular docking of metastable representative structures of DNA aptamers obtained from molecular dynamics (MD) simulation of distinct initial conformations.…”
Section: Introductionmentioning
confidence: 99%
“…Both these stages were accomplished using 25,000 steepest descent (SD) steps and 25,000 conjugate gradient (CG) minimization steps. Each system was then heated to 300 K in a 100 ps simulation performed at a constant volume with the RNA restrained using a 10 kcal mol –1 Å –2 force constant, using the Langevin temperature equilibration scheme. , This was followed by five independent 100 ns simulations on each of the four aptamer states using different initial velocities, which amount to a total of 2 μs of production simulation time . All production simulations were carried out in an NPT ensemble maintained at 300 K temperature and 1 atm pressure, using the Langevin thermostat and Berendsen barostat, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…59,60 This was followed by five independent 100 ns simulations on each of the four aptamer states using different initial velocities, which amount to a total of 2 μs of production simulation time. 61 All production simulations were carried out in an NPT ensemble maintained at 300 K temperature and 1 atm pressure, using the Langevin thermostat and Berendsen barostat, 62 respectively. The bonds involving hydrogen atoms were constrained using the SHAKE algorithm during the heating and production steps.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Although docking simulations are powerful techniques to elucidate 3D structures that are stable with respect to energetics, ideally one would also study the dynamics of these structures over time. MD simulations generate a conformational ensemble of nucleic acid structures at equilibrium and provide detailed atomic motions that aid in understanding structure–function relationships in an aptamer [ 112 , 114 ]. Due to the advantages of incorporating MD simulations into a computational pipeline, an increasing number of published studies report the use of software packages such as NAMD, AMBER, and GROMACS [ 101 , 115 , 116 ].…”
Section: Nucleic Acid Aptamersmentioning
confidence: 99%
“…Due to the advantages of incorporating MD simulations into a computational pipeline, an increasing number of published studies report the use of software packages such as NAMD, AMBER, and GROMACS [ 101 , 115 , 116 ]. Ultimately, computational methods could be applied to predict the interactions between an aptamer and its ligand and, hence, refine the nucleic acid sequence to improve the binding affinity and specificity, in addition to being applied for the de novo selection of aptamer in silico [ 114 , 116 ]. An overview of the workflow followed for the simulation-based prediction of an aptamer’s interactions with, and affinity for, its ligand is shown in Figure 2 .…”
Section: Nucleic Acid Aptamersmentioning
confidence: 99%